The Patient Journey in Medical Clinics: A Critical Analysis of Treatment Processes and Outcomes - Alanezi, Sarah Abdulaziz; Alnazi, Khulood Farhan; Almahboob, Sharefah saad; Alrasheedi, Badour Mansour; Alharbi, Sara Fahad; Alnazi, Nouf Ayed; ALanazi, Asma Dafi; Alotaibi, Maha Majeb (Journal of Ecohumanism, 2024)
The patient journey in medical clinics is a critical determinant of healthcare quality, efficiency, and patient satisfaction. This study critically analyzes the treatment processes within medical clinics, focusing on key stages such as appointment scheduling, diagnosis, treatment administration, and follow-up care. The analysis highlights inefficiencies in workflow management, long waiting times, administrative bottlenecks, and the impact of medical errors on patient outcomes. Additionally, the role of technology, including electronic health records and AI-driven decision support systems, is explored as a means to enhance efficiency and patient care quality. The study identifies best practices for optimizing treatment processes, such as Lean Six Sigma methodologies, patient-centered care models, and digital transformation strategies. By addressing existing challenges and proposing actionable solutions, this research aims to contribute to improving healthcare delivery and patient outcomes in medical clinics.